(untitled) (Journal of the College of Basic Education, 2023)
The study showed the ability of the fungus bassiana Beauvirea to control the different stages of the red cowpea beetle Callosobruchus maculatus by using the following different concentrations: 102, 104, 106 and the results were as follows: Concentration 102 exceeded in controlling the larvae of the second stage, while concentration exceeded 104 in controlling the larvae of the second stage. Fourth, focus 106 was more effective in female adults. The study also showed that the percentage of killing the different stages of the pest increases with the increase in the exposure period, and that the medium concentrations are more effective in controlling the pest.